(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Methamphetamine (METH), a highly addictive drug and a strong stimulant of the central nervous system. METH abuse is increasing, especially among young people and adolescents, and therefore we wanted in this research to shed light on some of the problems resulting from meth use, especially its effect on the central nervous system, the blood-brain barrier, and Fractalkine (CX3CL1). CX3CL1 is the only member of the CX3C subcategory of chemokines, which have a major role in the central nervous system by regulating interactions between neurons, glial cells, and immune cells. It is also considered heavily involved in traumatic brain injury (TBI) and spinal cord injury (SCI). The study was conducted on eighty people divided into three groups, thirty non addicted men as a control group(G1), taking into account and excluding, cigarette smoking, age, social and cultural conditions, and chronic diseases, also thirty people addicted to methamphetamine(G2), and twenty people addicted to methamphetamine and other narcotic substances (mix)(G3), whose ages ranged between (15-45) years and the period of methamphetamine abuse ranged between (1-7) years. The results of study showed that CX3CL1 values were higher among addicted persons compared to non addicts (G1), this difference in values shows us the effect of meth on the total values of CX3CL1.